Trait coordination and trade-offs constrain the diversity of water use strategies in Mediterranean woody plants - Francisco J. Muñoz-Gálvez; José I. Querejeta; Cristina Moreno-Gutiérrez; Wei Ren; Enrique G. de la Riva; Iván Prieto (Nature Communications)
Abstract The diversity of water-use strategies among dryland plants has been the focus of extensive research, but important knowledge gaps remain. Comprehensive surveys of water-use traits encompassing multiple species growing at contrasting sites are needed to further advance current understanding of plant water use in drylands. Here we show that ecohydrological niche segregation driven by differences in water uptake depth among coexisting species is widespread across Mediterranean plant communities, as evidenced by soil and stem water isotopes measured in 62 native species growing at 10 sites with contrasting climatic conditions. Foliar carbon and oxygen isotopes revealed that leaf-level stomatal regulation stringency and water-use efficiency also differ markedly among coexisting species, and are both coordinated with water uptake depth. Larger and taller woody species use a greater proportion of deeper soil water, display more conservative water use traits at leaf level (“water-savers”) and show greater investment in foliage relative to shoots. Conversely, smaller species rely mainly on shallow soil water, exhibit a more profligate water use strategy (“water-spenders”) and prioritize investment in shoots over foliage. Drought stress favours coordination between above and belowground water-use traits, resulting in unavoidable trade-offs that constrain the diversity of whole-plant water use strategies in Mediterranean plant communities.